Intervención temprana del personal de salud para la atención de la salud mental de la mujer durante el embarazo (2021)
In the course of history, maternal mental health disorders have been documented, initially related to punishments from the "gods" and supernatural episodes, until Hippocrates began to document cases related to puerperal sepsis and delirium, he was the first to speak of puerperal psychosis, all this he attributed to the theory of humors, the mental imbalance was related to the imbalance of the four liquids, in the case of postpartum he spoke of the rise of the lochia to the head which generated the Delirium, also associated with mental disorders, reported the first cases of neonaticides. (1,2) Several authors have delved into the studies and characteristics of mental health alterations in women in pregnancy and in the puerperium, realizing that it is a public health problem, since there is a set of variables that facilitate these alterations in pregnancy and biopsychosocial factors, due to the aforementioned, the importance of early interventions by health personnel in alterations in the mental health of women in pregnancy is recognized. (3–5)